2003
DOI: 10.1021/la026133a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling and Measuring the Interdependence of Local Properties in Biomembranes

Abstract: Local composition, structure, morphology, and phase are interrelated in lipid bilayer membranes. This work describes proofs-of-concept for methods that may be used and combined to modulate, to measure, and to probe the local structure of model membranes through control of membrane curvature in liposomes. These studies are performed using combinations of simultaneous two-color widefield fluorescence imaging, three-dimensional rendering of vesicle domains, and manipulation of the vesicle morphology via micropipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 54 publications
2
29
1
Order By: Relevance
“…In an initial experiment, after obtaining a fluorescence micrograph of the vesicle with the tubulin extension, we observed that the extended region of the membrane exhibited pearling and that the MT had depolymerized (19). Pearling was typically observed only at high 6-AS concentrations, and is consistent with the behavior of a membrane tether after the release of stress (20,21).…”
Section: Resultssupporting
confidence: 56%
“…In an initial experiment, after obtaining a fluorescence micrograph of the vesicle with the tubulin extension, we observed that the extended region of the membrane exhibited pearling and that the MT had depolymerized (19). Pearling was typically observed only at high 6-AS concentrations, and is consistent with the behavior of a membrane tether after the release of stress (20,21).…”
Section: Resultssupporting
confidence: 56%
“…that the generation and stability of the lipid bilayer tubes in the cellular and artificial multicomponent membrane systems in the absence of elongated inner stiff supporters , e.g. microtubules [23][27] or external pulling forces , such as, optical tweezers [28], [29] or motor proteins (kinesin, dynamin) [29], [30], can be explained by the presence of membrane elements (nanodomains) and attached proteins with anisotropic properties. As for example, the membrane attached crescent shaped BAR domain proteins have clearly anisotropic shape and therefore their energy depend on their local orientation or statistically averaged local orientation, depending on the local curvature of the membrane [5], [20], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods produce giant liposomes; these methods include “gentle hydration”,711 “freeze-and-thaw”,12,13 “solid hydration”,14 “solvent evaporation”,15,16 emulsion-based methods,17 and “electroformation” 1,2,9,1821. These methods generate giant liposomes of high quality and yield, but they are typically limited to solutions of low ionic strength (≤50 mM monovalent salt)1,3,710,16,22 unless specialized lipid formulations810 or specific electroformation protocols22,23 are used.…”
Section: Introductionmentioning
confidence: 99%